756 Assessment of the immune checkpoint landscape in head and neck squamous cell carcinoma by single-cell RNA sequencing and multispectral imaging. (9th November 2020) - Vujanovic, Lazar; Kulkarni, Aditi; Kürten, Cornelius; Cillo, Anthony; Santos, Patricia; Lang, Stephan; Duvvuri, Uma; Kim, Seungwon; Skinner, Heath; Bruno, Tullia; Vignali, Dario; Bao, Riyue; et al.
Abstract : Background: Resistance to the current generation of immunotherapies is mediated by complex relations between stromal, cancer and immune cells found within the tumor microenvironment (TME). Development of more efficacious drugs is predicated on improved understanding of these multi-spatial interactions. With emergence of new immune checkpoint receptor (ICR)-targeting therapies, a better understanding of topological expression of immune checkpoint ligand (ICL) on suppressive cell types in the TME may allow for improved strategies to treat cancer patients. Methods: Single cell RNA sequencing (scRNAseq) was performed from head and neck squamous cell carcinoma (HNSCC) specimens (n=18) with matched blood from treatment-naïve patients. Immune and non-immune cells were enriched from tumor cell suspensions. Novel transcriptomic cell-to-cell interactions were predicted between heterogeneous cell populations. Histologic inflammation was corroborated with scRNAseq and multiplex flow cytometry. Cell type-specific PD-L1 contributions within the TME were quantified using multispectral imaging. Results: Major cell type clusters (immune, epithelial, fibroblast and endothelial cells) were identified. Expression patterns for PD-1, TIGIT, LAG-3 and TIM-3 ligands were evaluated on these suppressive TME cell types. By modeling receptor-ligand interactions between CD8+ T cells and the rest of the major TME cell types, CD8+ T cells were predicted to form more ICR-ICL interactions with tumor-associated macrophages (TAMs) than with any other cell type. With focus on LGALS9/galectin-9 and CD274/PD-L1, flow cytometric analyses validated the scRNAseq observation that both ligands were expressed on TAMs from both inflamed and non-inflamed tumors. Furthermore, flow cytometry and multispectral imaging analyses implicated macrophages as one of the major contributors of CD274/PD-L1 within the TME. Conclusions: Our data suggest that in the setting of HNSCC, TAMs are one of the major contributors of ICL in the HNSCC TME. Strategies that selective target this immunosuppressive population may be necessary to break tolerance to PD-1-targeting therapies. Ethics Approval: The study was approved by the UPMC Hillman Cancer's Ethics Board, approval number 99-069.